KID Syndrome Complicated by Multiple Abscesses of the Parietal Region Skin: Clinical Case - Anastasia A. Bebenina; Madina A. Chundokova; Alexey N. Smirnov; Maxim A. Golovanev; Alina A. Dokshukina (Вопросы современной педиатрии, 2021)
Background. KID syndrome (keratitis-ichthyosis-deafness) is an orphan genetic multisystem disease with autosomal recessive and dominant types of inheritance, it manifests in the neonatal period. The leading triad of symptoms is: skin lesions, ophthalmological diseases and hearing organ pathology. Clinical Case Description. Girl V., 17 years old, with KID syndrome applied to the hospital complaining on painful infiltrates of the parietal region. Multiple abscesses were lanced. Hyperkeratotic crusts were removed, unviable skin regions were excised, and abscesses' cavities were washed with antiseptic solution during daily dressings. Purulent discharge from wounds has been maintaining for 7 days. Conclusion. Where is no pathogenetic treatment for KID syndrome yet. Prevention of secondary surgical infections remains the crucial aspect in the management of such patients. Local wound treatment, symptomatic and antibacterial therapy are effective in case of skin infection.